Explaining Power Over the Investee - the Rights that Give the Possibility to Directs the Investee`s Relevant Activities - VIORICA MIRELA STEFAN-DUICU (Global Economic Observer)
The links created on all levels between the parent company and its subsidiaries have generated along time debates regarding the regulations applicable in the audit activity in order to protect the above mentioned entities. Throughout this paper we will progressively describe the pylons that represent the foundation of the regulations subject to the audit activity in this organizational environment.